GMT PARA CARTOGRAFIAR LA VARIABILIDAD EN EL ENTORNO GEOLÓGICO Y LA BATIMETRÍA DEL OCÉANO PACÍFICO - Lemenkova, Polina (Mercator, 2021)
The paper presents spatial analysis of the geological settings and topographic structure of the Pacific Ocean by Generic Mapping Tools (GMT). The tectonic and geomorphic features of the Pacific Ocean have a complex character and include trenches, ridges, East Pacific Rise, basins, fracture zones, rifts, rises, fault systems. As a result, the seafloor fabric has a variability in sedimentation reflecting correlations between the tectonic geomorphic markers and bathymetry. The Pacific Ocean is the largest ocean on the Earth wit structural features of the seafloor playing an important role in global geomorphology. The methodology is based on the advanced cartographic toolset GMT which utilizes a shell scripting approach using a variety of modules. Data analysis was based on the comparison of high-resolution grids: 1 arc-min ETOPO1, 5-arc min GlobSed, 1-arc min gravity. The geological settings of the Pacific Ocean seafloor are referenced to the thematic layers plotted by GMT: Galapagos Rift, Eltanin and Menard Fault Systems, Gorda and Juan de Fuca ridges, fracture zones. The seabed regions characterized by the correlation in fault and fracture zones with tectonic delineations were identified. Variations of depths were compared with gravity and discussed. It was found that the rift zone of the South and East Pacific rises correlates with the topographic isolines. The tectonics showed strong correlation with the seafloor topography, and a weaker correlations with sedimentation, influenced by geomorphology, location, gravity anomalies and bathymetry. The paper contributes to the oceanographic and geologic studies of the Pacific Ocean and methodology of GMT. Specifically, five GMT scripts are presented for a reference and repeatability in similar geomatic research.